Towards Economical E-Learning Educational Environments for Physically Challenged Students - Zeid, Amir; Sakit, Sarah S.; Al-AbdulRazzaq, Noor A.; Al-Tattan, Mariam M.; Sakit, Fatima S.; Amin, Abrar; Al-Najdi, Mariam; Al-Rowaished, Aisha (IntechOpen, 2012)
None